دراسة استقصائية حول استعمال النباتات الطبية في علاج القرحة المعدية لمنطقة الوادي و المغير – الجزائر - بن قسوم لطيفة (جامعة الوادي university of eloued, 2025)
In recent years, there has been a growing interest in traditional medicine, particularly the use of medicinal plants in managing chronic conditions such as gastric ulcers. This disorder is among the most common gastrointestinal diseases and is associated with multiple factors, including bacterial infection, prolonged use of anti-inflammatory drugs and psychological stress. In this context, medicinal plants have emerged as an alternative or complementary therapeutic option due to their bioactive compounds with antioxidant and anti-inflammatory properties, necessitating scientific assessment of their effectiveness within local populations. This field-based survey aims to document the patterns of medicinal plant use in treating gastric ulcers in the regions of El Oued and El M’Ghair, Algeria, through the distribution of 263 questionnaires among diverse demographic and occupational groups. The study focused on identifying the most frequently used plant species, preparation methods, sources of procurement, and frequency of use, in addition to evaluating individuals’ perceptions of therapeutic efficacy. A descriptive analytical approach was employed, enabling the collection of direct field data that reflect local health behaviors and cultural practices. The findings revealed a high reliance on medicinal plants such as pomegranate, thyme, and chamomile for managing ulcer-related symptoms, with a noticeable improvement reported by the majority of users. Results also indicated a predominant dependence on herbalists as the main source of plants, alongside limited medical consultation or clinical diagnosis. These outcomes highlight the strong cultural anchoring of herbal medicine in the region, while underscoring the need for further scientific research to evaluate such practices through standardized pharmacological frameworks.
علم النبات
Keywords: Medicinal plants - Gastric ulcers - Traditional medicine - Survey - Therapeutic efficacy - Herbal remedies